An economic evaluation of outpatient versus inpatient polyp treatment for abnormal uterine bleeding. (25th May 2015) - Diwakar, L; Roberts, TE; Cooper, NAM; Middleton, L; Jowett, S; Daniels, J; Smith, P; Clark, TJ; ,
Abstract : Objectives: To undertake a cost‐effectiveness analysis of outpatient uterine polypectomy compared with standard inpatient treatment under general anaesthesia. Design: Economic evaluation carried out alongside the multi‐centre, pragmatic, non‐inferiority, randomised controlled Outpatient Polyp Treatment (OPT) trial. The UK National Health Service (NHS) perspective was used in the estimation of costs and the interpretation of results. Setting: Thirty‐one secondary care UK NHS hospitals between April 2008 and July 2011. Participants: Five hundred and seven women with abnormal uterine bleeding and hysteroscopically diagnosed endometrial polyps. Interventions: Outpatient uterine polypectomy versus standard inpatient treatment. Clinicians were free to choose the technique for polypectomy within the allocated setting. Main outcome measures: Patient‐reported effectiveness of the procedure determined by the women's self‐assessment of bleeding at 6 months, and QALY gains at 6 and 12 months. Results: Inpatient treatment was slightly more effective but more expensive than outpatient treatment, resulting in relatively high incremental cost‐effectiveness ratios. Intention‐to‐treat analysis of the base case at 6 months revealed that it cost an additional £9421 per successfully treated patient in the inpatient group and £ 1, 099, 167 per additional QALY gained, when compared with outpatient treatment. At 12 months, these costs were £22, 293 per additional effectively treated patient and £445, 867 per additional QALY gained, respectively. Conclusions: Outpatient treatment of uterine polyps associated with abnormal uterine bleeding appears to be more cost‐effective than inpatient treatment at willingness‐to‐pay thresholds acceptable to the NHS. Tweetable abstract: HTA‐funded OPT trial concluded that outpatient uterine polypectomy is cost‐effective compared with inpatient polypectomy. Tweetable abstract: HTA‐funded OPT trial concluded that outpatient uterine polypectomy is cost‐effective compared with inpatient polypectomy.